Pengaruh Konsentrasi Fosfat Terhadap Perbandingan Ca/P Hidroksiapatit dari Limbah Gipsum Industri Keramik - Asep Mufti Kurniawan; Sri Hartini; Margareta Novian Cahyanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Gypsum waste has the potential to be made into hydroxyapatite (HAp). In this study synthesis of HAp with hydrothermal method using microwave at heating temperature of 100 ºC was carried out. The purpose of this study was to obtain hydroxyapatite bioceramic compounds from gypsum waste, determine the ratio of Ca/P in obtained HAp and characterizing the obtained HAp. HAp characterization has been carried out using FTIR and XRD. The result showed that 2,5 grams of gypsum powder produced HAp powder yield of 65,61% to 84,43%. Calcium levels are 0,02440 % to 0,03466 %, while phosphate levels are 0,038 % to 0,055 %. The Ca/P ratio are 0,28 to 0,39. FTIR HAp characterization results indicate the presence of phosphate groups (PO43-), hydroxyl groups (OH-), and Ca-O groups. But based on XRD analysis, The HAp obtained is not a standard HAp.